Reflections on casualization and pathways to reprofessionalize the professoriate: a conversation between communication studies colleagues. Issue 2 (3rd April 2018) - Foust, Christina R.; Lair, Daniel J.
ABSTRACT: This essay considers academic labor in communication studies through the lens of Michael Bérubé and Jennifer Ruth's The Humanities, Higher Education, and Academic Freedom . Bérubé and Ruth argue that, by and large, knowledge production in the humanities is in "fine shape, " but that the decades-long trend away from tenure-track towards contingent faculty employment has "hollowed out" the profession of college teaching—a de-professionalization that departments, disciplines, and institutions have yet to fully reckon with. We find Bérubé's and Ruth's policy prescription for this exigent moment—the creation of a teaching-intensive tenure-track for contingent faculty—to be a provocative frame through which to begin addressing casualization in communication studies. Our hope is to spark conversation in response to a rather large question: At a time when every profession, from law to medicine to journalism, faces varying degrees and consequences of casualization, what would it mean to reprofessionalize ourselves, as communication studies faculty?